BIOLOGICAL ACTIVITY OF QUINAZOLINONE DERIVATIVES: A REVIEW - M., WAGHMARE SWEETI; M., MANCHARE AKANKSHA; Y., SHAIKH AVESH; G., DIKSHA RAUT (International Journal of Current Pharmaceutical Research, 2023)
The heterocyclic compounds have a great importance in medicinal chemistry. Quinazolinone is a heterocyclic chemical compound. A quinazolinone with a carbonyl group in the C4N2 ring. The two isomers are possible: 2-Quinazolinone and 4-Quinazolinone, with the 4-isomer being the more common. These compounds are of interest in medicinal chemistry. Quinazolinone derivatives were reported to possess analgesic and anti-inflammatory activity, Antibacterial, Diuretic, Antihypertensive, Anti-diabetics, Anticancer, Antitumor, Anti-fungal, Anti-malarial, Anti-protozoal agent and many other biological Action. This skeleton is an important pharmacophore considered as a privileged structure.